2012
DOI: 10.1016/j.molcel.2011.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis Reveals that Noncoding RNAs Contribute to Clonal Heterogeneity by Modulating Transcription Factor Recruitment

Abstract: Summary Mechanisms through which long intergenic noncoding RNAs (ncRNAs) exert regulatory effects on eukaryotic biological processes remain largely elusive. Most studies of these phenomena rely on methods that measure average behaviors in cell populations, lacking resolution to observe the effects of ncRNA transcription on gene expression in a single cell. Here, we combine quantitative single-molecule RNA FISH experiments with yeast genetics and computational modeling to gain mechanistic insights into the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 39 publications
1
91
1
1
Order By: Relevance
“…Rpd3 activates FLO11 expression by repression of ICR1 ncRNA and Sfl1 has the opposite role (Bumgarner et al 2009(Bumgarner et al , 2012. We have observed that this effect of Rpd3 is not shared by Hos2, suggesting that this effect may be the additional mechanism independent of Hos2 observed for Rpd3.…”
Section: Activation Of Flo11 By Both Rpd3 and Hos2mentioning
confidence: 65%
See 1 more Smart Citation
“…Rpd3 activates FLO11 expression by repression of ICR1 ncRNA and Sfl1 has the opposite role (Bumgarner et al 2009(Bumgarner et al , 2012. We have observed that this effect of Rpd3 is not shared by Hos2, suggesting that this effect may be the additional mechanism independent of Hos2 observed for Rpd3.…”
Section: Activation Of Flo11 By Both Rpd3 and Hos2mentioning
confidence: 65%
“…Sfl1 activates ICR1 ncRNA transcription by repressing the transcription of PWR1 ncRNA that partially interferes with the ICR1 one. In this interesting regulatory mechanism, the Rpd3L complex has been described to have the opposite role (Bumgarner et al 2009(Bumgarner et al , 2012. We carried out qRT-PCR to study the level of ICR1 ncRNA in mutants from both backgrounds ( Figure 6B) and to study the effect of histone deacetylases and Sfl1 over this regulation.…”
Section: Deacetylase Activity Of Rpd3 Is Required For Flo11 Expressionmentioning
confidence: 99%
“…This repression of IME1 by IRT1 transcription is dependent on Set2 methyltransferase and Set3 deacetylase, suggesting that histone modifications are critical here. The FLO11 gene encodes a cell wall protein regulating adhesion between cells, and its expression is controlled by a pair of lncRNAs from the upstream region (24). lncRNAs have been proposed to regulate gene induction at the PHO5 (22) and GAL loci (21,52).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) can regulate transcription (14)(15)(16)(17), and in budding yeast lncRNAs have been implicated in promoter regulation (18)(19)(20)(21)(22)(23)(24). Here we decipher the mechanism by which mating pheromone blocks expression of the HO endonuclease during the subsequent cell cycle.…”
Section: Significancementioning
confidence: 99%
“…In addition to these pathways, FLO11 is also regulated by the pH response pathway, noncoding RNAs, and the chromatin state (Halme et al 2004;Barrales et al 2008Barrales et al , 2012Bumgarner et al 2009;Octavio et al 2009). A recent study showed that the noncoding RNAs contribute to a variegated transcription of FLO11 through the modulation of transcription factor recruitment (Bumgarner et al 2012).The FLO genes share a common structure, including a C-terminal glycosylphosphatidylinositol (GPI)-anchor addition site, an N-terminal carbohydrate-or peptide-binding domain or domain of unknown function, and a central domain containing multiple serine and threonine-rich repeats (Verstrepen and Klis 2006). The latter domain is also referred to as a domain with intragenic tandem repeats.…”
mentioning
confidence: 99%